Effect of Principal Leadership and Teacher Commitment on Teacher Performance Through Organizational Culture - Puspitaningrum, Erlina Dewi; Yusuf, Amin; Yanto, Heri (Educational Management, 2021)
Education plays an important role in the process of improving human resources (HR). Human resources are the factors that have the biggest role in achieving organizational goals effectively and efficiently. This research aims to determine the effect of principal's leadership and teacher commitment on teacher performance with organizational culture as the mediating variable for public high school teachers in Kudus Regency. The sampling technique used is proportionate random sampling with a total sample of 207 teachers taken from seven public schools in Kudus Regency. Data analysis employes path analysis with the help of AMOS 24.0 program. Questionnaire is used as the instrument of data collection. The results show that principal's leadership and teacher commitment directly affect organizational culture; principal's leadership and organizational culture affect teacher performance; teacher commitment does not affect teacher performance; and principal's leadership affects teacher commitment. As for the indirect effect, organizational culture is able to mediate the effect of principals' leadership on teacher performance, while organizational culture is not able to mediate the effect of teacher commitment on teacher performance.